2020
DOI: 10.1101/2020.10.02.20205708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antigen-based testing but not real-time PCR correlates with SARS-CoV-2 virus culture

Abstract: Individuals can test positive for SARS-CoV-2 by real-time polymerase chain reaction (RT-PCR) after no longer being infectious.1-8 Positive SARS-CoV-2 antigen-based testing exhibits a temporal pattern that corresponds with active, replicating virus and could therefore be a more accurate predictor of an individuals potential to transmit SARS-CoV-2.2,3,9 Using the BD Veritor System for Rapid Detection of SARS-CoV-2 later flow antigen detection test, we demonstrate a higher concordance of antigen-positive test res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 37 publications
6
84
0
Order By: Relevance
“…Although the correlation between viral load and transmissibility is not entirely clear, several studies showed that samples with higher viral loads of ≥6 log 10 RNA copies/mL were likely to correlate with infectivity in cell culture models [ 15 , 25 , 26 , 27 , 28 ]. We, and others, showed that Ag-RDTs, although less sensitive, align better with cell culture-based testing for infectivity than rRT-PCRs [ 14 , 25 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 96%
“…Although the correlation between viral load and transmissibility is not entirely clear, several studies showed that samples with higher viral loads of ≥6 log 10 RNA copies/mL were likely to correlate with infectivity in cell culture models [ 15 , 25 , 26 , 27 , 28 ]. We, and others, showed that Ag-RDTs, although less sensitive, align better with cell culture-based testing for infectivity than rRT-PCRs [ 14 , 25 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 96%
“…RAD tests are simple to carry out and return results within a short time, thus being well-suited for point-of-care testing (POCT). Moreover, two recently evaluated RAD assays (BD Veritor System and the Panbio™ COVID-19 Ag Rapid Test Device) may be used as a proxy for SARS-CoV-2 cultured from respiratory tract specimens, thus allowing reasonably accurate prediction of contagiousness [ 2 , 3 ]; yet this assumption awaits further validation in larger cohorts. The possibility of using RAD tests to identify SARS-CoV-2-infected asymptomatic contacts of COVID-19 patients is appealing, as it could effectively contribute to minimize community SARS-CoV-2 spread through early detection of highly infectious individuals [ 1 ], yet little is known about how RAD tests perform in this population group [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 tests include molecular tests such as qPCR, isothermal amplification, and CRISPR, as well as antigen tests that detect SARS-CoV-2 proteins directly. Although rapid antigen tests have lower analytical sensitivity (i.e., require greater amounts of virus material to turn positive) than qPCR-based tests, their ability to detect infectious individuals with culturable virus is as high as for qPCR (3). Specificity (i.e., correctly identifying those not infected with SARS-CoV-2) of antigen tests achieves comparable results to molecular tests (4).…”
mentioning
confidence: 99%